Peran Persepsi Keadilan dalam Hubungan Reward, Punishment, dan Kinerja Karyawan pada PT. Rezeki Perkasa Sejahtera Lestari - Maulana Filani Rizal; Febrianawati Febrianawati; Irvan Wibowo W; Yuana Yuana; Indera Areskeia (Riwayat: Educational Journal of History and Humanities, 2025)
Abstrak:This study investigates the influence of reward and punishment policies on employee performance at PT. Rezeki Perkasa Sejahtera Lestari, specifically examining the mediating role of perceived justice. Ineffective leadership, often stemming from poorly managed reward and punishment systems, significantly impacts employee performance. A quantitative approach was employed, collecting data from 35 employees via questionnaires distributed through Google Forms. Path analysis using SmartPLS 8.0 was utilized for data analysis. The findings reveal that while reward and punishment directly show a weak and non-significant impact on employee performance, perceived justice positively and significantly influences performance (H3 accepted). Reward also shows a weak but positive influence on perceived justice (H4 rejected at =0.05, but with a weak significance tendency at =0.10), suggesting an indirect effect on performance through perceived fairness. Conversely, punishment's impact on both performance (H2 rejected) and perceived justice (H5 rejected) was found to be insignificant, indicating potential inefficiencies in its application. This research highlights the critical importance of fairness in human resource management and recommends that companies prioritize the perceived justice of their reward and punishment systems to enhance employee performance effectively. Future research should verify this model in similar companies and explore the specific mediation mechanisms of perceived justice.